Aspect-oriented analysis for software product lines requirements engineering - Varela, Patrícia (2013)
Requirements analysis and modeling for Software Product Lines demands the use of feature models, but also requires additional models to help identifying, describing, and specifying features. Traditional approaches usually perform this manually and, in general, the identification and modularization of crosscutting features is ignored, or not handled systematically. This hinders requirements change. We propose an aspect-oriented approach for SPL enriched to automatically derive feature models where crosscutting features are identified and modularized using aspect-oriented concepts and techniques. This is achieved by adapting and extending the AORA (Aspect-Oriented Requirements Analysis) approach. AORA provides templates to specify and organize requirements based on concerns and responsibilities. A set of heuristics is defined to help identifying features and their dependencies in a product line. A tool was developed to automatically generate the feature model from AORA templates.